Blue water footprint based on industrial activities in Kuantan River Basin - Amirul Asyraf, Borhan (2018)
Around the globe, millions of people are greatly in danger of not having enough food and water supply, weakening the very basic foundation of local, national and global stability. Competition for scarce resources – especially water- is increasing, aggravate the old security dilemmas and creating new ones. Thus, this study aimed to determine the blue water footprint for industrial activities in Kuantan River Basin and to identify the effect of land use development to the accounting of blue water footprint from 2015 until 2017. Next, to forecast the sustainability of Water Supply Treatment Process in Kuantan River Basin. Therefore, in order to achieve the stated objectives, total water footprint from each water treatment plant will be counted and the distribution of land use development will be analysed. A series of modelling using ANN – an Artificial Intelligence (AI) application tolls in Matlab. Hence, the results of amount blue water footprint, effect of land use development and the future value of predicted water footprint shall be determined.